sPring 98 : Jong Talent uit Antwerpen. - Koningin Fabiolazaal, Antwerpen; Meurrens, Luc; Paulus, Camille; Walgrave, Jan (Antwerpen : [s.n.], 1998)
Brouckaert, Hedwig ; Cotteleer, Erika ; Daems, Myriam ; De Beul, Anne-Marie ; De Clerck, Sandra ; De Cupere, Peter ; De Schryver, Marie-Bénédicte ; Denys, Francis ; Emmerich, Hadassah ; Goiris, Geert ; Hanssen, Hildegard ; Liekens, Ilse ; Stickers, Inge ; Van Den Broek, Koen ; Van Dijck, Hans ; Van Herck, Elke ; Wuyts, Katrien
Koningin Fabiolazaal, Antwerpen, 10 april - 3 mei 1998
kunstcatalogus